Degradation kinetics of ascorbic acid in peach nectar during thermal processing - Cedeño-Sares, Luis; Díaz-Torres, Raúl; Núñez-Quezada, Thayana; Armijos-Cabrera, Gabriela; Cruz-Viera, Luis (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Ascorbic acid is a beneficial component for health, but it is degraded during the thermal pasteurization of food products. The aim of this research was to determine the influence of temperature on the thermal degradation of ascorbic acid in peach nectar at 75, 85 and 95 °C, evaluating this effect at 0, 30, 60, 90 and 120 minutes. The degradation of ascorbic acid follows a first order reaction model with rate constants that vary between 5.5 to 10.9 x 10-3 min-1. D-Values ranged from 211.28 to 418.73 min, while Z value was 69.4 oC. The values of the free energy of inactivation ranged between 112.63 and 117.17 kJ.mol-1, while for the activation enthalpy the values varied between 25.37 and 25.54 kJ.mol-1 and the range for the activation entropy was from -249.36 to -250.15 J.mol-1.K-1.It can be concluding that the reaction is endothermic and does not occur spontaneously. The knowledge of these values is important not only to explain the loss of ascorbic acid, but also to design and optimize thermal processes aimed at preserving the nutritional quality of peach nectar.